Editorial Introduction - Gordon Wells (Networks: An Online Journal for Teacher Research, 2003)
It gives me particular pleasure to introduce this special issue by members of the Developing Inquiring Communities in Education Project (DICEP). For eight years, while I was at the Ontario Institute for Studies in Education/University of Toronto, I was a member of DICEP, and even now I still continue my participation - from a distance. Without any doubt, DICEP has been the major influence on the work I have been doing during the last decade.